2017
DOI: 10.1080/21691401.2017.1414825
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical aspects of silver nanoparticles

Abstract: Silver nanoparticles are particles in the size ranging between 1 and 100 nm. The two major methods used for synthesis of silver nanoparticle are the physical and chemical methods with the disadvantage that they are expensive and can also have toxicity. Biological method is being used as an expedient alternative, as this approach is environment-friendly and less toxic and it includes plant extracts, microorganism, fungi, etc. The major applications of silver nanoparticles in the medical field include diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
179
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 285 publications
(191 citation statements)
references
References 73 publications
4
179
0
8
Order By: Relevance
“…We also assessed the cytotoxic effects of fructose‐coated AgNPs (F‐AgNPs; F‐AgNPs diameter: 52.75 ± 5.25 nm, AgNPs diameter: 32.60 ± 3.48 nm) on cancer cell lines including BxPC‐3, PC‐3, CNE1, SW480, EC109, and MDA‐MB‐231 by CCK‐8 assay. The results showed that F‐AgNPs exhibited a much lower ability than F‐AgÅPs to inhibit the viability of these cancer cells with IC 50 values >40.5 ng µL −1 (Figure S1b, Supporting Information), which was consistent with the data of previous studies showing that the smaller particles usually have a stronger cytotoxicity . Interestingly, F‐AgÅPs did not show remarkable effects toward many human normal cell lines including vascular smooth muscle cells (VSMC), human microvascular endothelial cells (HMEC), hepatocytes (LO2), and embryonic kidney cells (293FT), resulting in high median IC 50 values (Figure S1c, Supporting Information).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…We also assessed the cytotoxic effects of fructose‐coated AgNPs (F‐AgNPs; F‐AgNPs diameter: 52.75 ± 5.25 nm, AgNPs diameter: 32.60 ± 3.48 nm) on cancer cell lines including BxPC‐3, PC‐3, CNE1, SW480, EC109, and MDA‐MB‐231 by CCK‐8 assay. The results showed that F‐AgNPs exhibited a much lower ability than F‐AgÅPs to inhibit the viability of these cancer cells with IC 50 values >40.5 ng µL −1 (Figure S1b, Supporting Information), which was consistent with the data of previous studies showing that the smaller particles usually have a stronger cytotoxicity . Interestingly, F‐AgÅPs did not show remarkable effects toward many human normal cell lines including vascular smooth muscle cells (VSMC), human microvascular endothelial cells (HMEC), hepatocytes (LO2), and embryonic kidney cells (293FT), resulting in high median IC 50 values (Figure S1c, Supporting Information).…”
Section: Resultssupporting
confidence: 88%
“…Alternatively, nanoparticles can passively penetrate the cell membranes and invade subcellular compartments, owing to their small size . Nanoparticles with smaller size have a much stronger penetration ability and greater cytotoxicity, which may better explain why F‐AgÅPs exhibited more potent anticancer effects than F‐AgNPs. Very small particles may, however, easily extravasate across the normal endothelium (that requires sizes less than 1–2 nm) into the surrounding healthy tissues and be rapidly cleared by the kidney as the threshold for the first‐pass elimination by the kidney is around 10 nm .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the preparation of NPs colloidal solution implies a solvent, a metal source, a reductant and a stabilizer. Several recent review papers describe the different strategies to design NPs, more specifically silver ones for biomedical applications [53][54][55][56][57][58]. In some cases, a unique compound can be used as solvent, reductant and stabilizers or as reductant and stabilizer-e.g., polyol process or citrate-based approach, respectively [59].…”
Section: Nanoparticles Definitionmentioning
confidence: 99%